Native-Land.ca | Our home on native land

Frontier life: borderlands, settlement & colonial encounters - Adam Matthew Publications
Keywords: _UdeM only

Independent Voices
About this Collection: Independent Voices is an open access digital collection of alternative press newspapers, magazines and journals, drawn from the special collections of participating libraries. These periodicals were produced by feminists, dissident GIs, campus radicals, Native Americans, anti-war activists, Black Power advocates, Hispanics, LGBT activists, the extreme right-wing press and alternative literary magazines during the latter half of the 20th century. Independent Voices is ma...
Keywords: _open access

North American Indian Thought and Culture - Alexander Street Press
Écrits personnels (journaux intimes, lettres, comptes rendus de conférences, etc.) de femmes canadiennes et américaines, de la période coloniale à 1950. Inclut biographies et bibliographies.
Keywords: _UdeM only